THE ROLE OF FARMERS GROUPS IN INCREASING SUSTAINABLE RICE PADDY FARMING BUSINESS IN LUBUK BAYAS VILLAGE OF PERBAUNGAN SUBDISTRICT - Nomi Noviani; Sri Wahyuni; Leni Handayani; Bambang Hermanto (Teunuleh Publisher, 2021)
Farmer groups as a forum for organization and collaboration between members have a very important role in the life of the farming community, because all activities and problems in farming are carried out by groups simultaneously. With the existence of farmer groups, farmers can jointly solve problems which include the fulfillment of agricultural production facilities, technical production and marketing of products. Seeing this potential, farmer groups need to be fostered and empowered further in order to develop optimally. In increasing rice production, it is necessary to preserve the production environment, one of which is through the use of organic fertilizers. Various forms and materials of organic fertilizer can be applied depending on the availability at the farm location. In an effort to improve sustainable farming, The things that are applied are increasing productivity in farming activities and the use of superior seeds, the use of fertilizers, pesticides and the application of cooperation for the manufacture of fertilizers so that group members do not need to buy fertilizer. The existence of institutions/KUD in a village is very helpful for farming communities because these institutions can also take capital loans for farmers so that farmers are able to provide good production facilities, which so far farmers have only relied on outside capital, which is not certain whether they can afford it. continue to cooperate with farmer groups.